Criminal risk associated with failed transactions: examining the rise of transactional relationships among financially strained students in higher education - Molokomme, Radiakga Thabang (Edelweiss Applied Science and Technology, 2025)
Love for sale or survival at stake? The rise of Mavuso relationships among financially strained students in higher education (HE) exposes them to significant criminal risks, including allegations of fraud, coercion, and rape when financial expectations go unmet. This study critically examines these risks and explores the socio-economic drivers of transactional relationships and their legal and ethical implications. Using a qualitative, desktop research approach, the study analyzed existing legal frameworks, case law, and scholarly literature to assess institutional responses and policy gaps. Findings reveal that ambiguous legal definitions, inadequate protections, and financial vulnerability exacerbate students’ exposure to exploitation. Moreover, the absence of clear institutional policies in HE institutions heightens the risks of criminalization and victimization. The study recommends legal reforms, enhanced financial support, ethical relationship education, and institutional interventions to mitigate these risks. Addressing these gaps is crucial to safeguarding student well-being, promoting ethical engagement, and shaping policies that protect vulnerable students from exploitation in transactional relationships.